Halal Tourism Destination Branding, Is It Important? - Fauzan al-Mansyur; Slamet Slamet; Zaenu Mahmudi (IQTISHODUNA, 2019)
This study aims to reveal the responses of tourism destination stakeholders to the branding of halal tourist destinations. The study was conducted in the largest tourist destination in East Java, Indonesia. In this study, the key informants are the Chair of the Indonesian Ulema Council, the Chair of the Regional People's Representative Council, tourism managers, and tourism destination business actors. The last two informants are those who understand the characteristics and behavior of tourists visiting tourism destinations. Data were obtained from primary data sources through non-participant observation and in-depth interviews using the Snow-ball Sampling approach. Sources of secondary data obtained through documents from agencies relevant to the research. Data analysis used descriptive-analytical approach and interpretation. The main finding of this research is the rejection of the branding of halal tourist destinations, which is stated explicitly even though the government has made policies and promotes branding of halal tourist destinations. Research on halal destinations is still very little and not popular, many think that the inclusion of halal labels is only intended for Muslim visitors